(untitled) (Lundiana: International Journal of Biodiversity, 2005)
Aculepeira angeloi sp. n. is described based on specimens found in nests of Trypoxylon (Trypargilum) lactitarse Saussure from the Ecological Station of the Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brazil.